A Phase IIb Study of ABT‐494, a Selective JAK‐1 Inhibitor, in Patients With Rheumatoid Arthritis and an Inadequate Response to Anti–Tumor Necrosis Factor Therapy. Issue 12 (December 2016) - Kremer, Joel M.; Emery, Paul; Camp, Heidi S.; Friedman, Alan; Wang, Li; Othman, Ahmed A.; Khan, Nasser; Pangan, Aileen L.; Jungerwirth, Steven; Keystone, Edward C.
Abstract : Objective: To compare the efficacy and safety of ABT‐494, a novel selective JAK‐1 inhibitor, with placebo in patients with moderate‐to‐severe rheumatoid arthritis (RA) and an inadequate response or intolerance to at least 1 anti–tumor necrosis factor (anti‐TNF) agent. Methods: In this 12‐week, double‐blind, placebo‐controlled, dose‐ranging study, 276 RA patients receiving a stable dose of methotrexate (MTX) who had previously received treatment with at least 1 anti‐TNF agent were randomized equally to receive immediate‐release ABT‐494 at 3, 6, 12, or 18 mg twice daily or matching placebo twice daily. The primary end point was the proportion of patients meeting the American College of Rheumatology 20% improvement criteria (achieving an ACR20 response) at week 12. Results: At week 12, significantly more patients receiving ABT‐494 (53–71%) than those receiving placebo (34%) achieved an ACR20 response (by nonresponder imputation analysis) ( P < 0.05), with a dose‐response relationship among all ABT‐494 doses ( P < 0.001). ACR50 and ACR70 response rates were significantly higher in those receiving ABT‐494 (36–42% and 22–26%, respectively) than in those receiving placebo (16% and 4%, respectively). Changes from baseline in the Disease Activity Score in 28 joints using the C‐reactive protein level (DAS28‐CRP) were significantly greater for all doses of ABT‐494 than for placebo ( P ≤ 0.01). Onset of action of ABT‐494 was rapid, with significant differences from placebo at week 2 both in ACR20 response rate (for 12 and 18 mg) and in change in the DAS28‐CRP ( P < 0.001 for 6–18 mg). The most frequent adverse events (AEs) were headache, nausea, upper respiratory tract infection, and urinary tract infection. Infection rates were higher at higher doses of ABT‐494, but no infections were serious. No deaths were reported among those receiving ABT‐494. Conclusion: In patients with an inadequate response or intolerance to anti‐TNF agents, ABT‐494 added to MTX showed rapid, dose‐dependent improvements in RA signs and symptoms, with safety and tolerability similar to those of other drugs of this class. No new AEs were identified.